Prototype of Temperature, Humidity and Fire Detection Monitoring System in Rice Warehouse Based on ESP32 Microcontroller - Anggraini, Dewi; Fitriani, Endah; Paramytha, Nina; Dasmen, Rahmat Novrianda (Politeknik Negeri Batam, 2025)
Rice warehouses in Indonesia experience significant post-harvest losses, reported to reach 10–20% annually, primarily due to poor environmental control and fire incidents. This study develops and evaluates an Internet of Things (IoT)-based environmental monitoring prototype for rice warehouses, utilizing the ESP32 microcontroller, DHT22 temperature-humidity sensor, and a flame sensor. The ESP32 was chosen for its low power consumption and robust connectivity, while DHT22 and the flame sensor were selected for their balance of accuracy, sensitivity, and cost-effectiveness. System calibration employed a digital thermohygrometer and a standard flame detector to ensure measurement validity. Experimental tests were conducted in a controlled laboratory setting with three sensor points, simulating temperature variations of 28–45°C and humidity of 60–95%, together with 24-hour reliability tests and scenarios involving fire detection at a 30 cm distance. The system achieved sensor error margins within ±0.5°C for temperature and ±2% for humidity, with actuator response times of 1–3 seconds. Real-time Telegram notifications were successfully delivered within 2–3 seconds. The integration of multi-sensors, automated actuators, and instant notifications distinguishes the proposed system from conventional approaches and previous studies. While effective for small-to-medium scale warehouses, limitations remain in fire sensor coverage and dependence on internet connectivity. The system offers an adaptable, efficient, and reliable solution to minimize manual errors and improve rice warehouse management. Future work will address broader scalability, additional gas sensors, GSM communication, and cloud-based data logging for enhanced safety and analytics.